A GaN–Si hybrid integrated driver for narrow-pulse and high-current LiDAR applications - Chang, Yukuan; Yuan, Fang; Kou, Yuxia; Zhang, Xu (Frontiers in Physics, 2022)
Light detection and ranging (LiDAR) is the most important active remote sensing tool and is widely used in civilian and military fields. There are a number of methods to drive laser diodes; the most common circuit topologies are capacitor-discharge resonant circuits. However, the performance of the silicon (Si)-based switching device limits the development of LiDAR, such as the large figure of merit (FOM) and the stray inductance. Although different methods have been reported to resolve these problems, there are still great challenges in reducing the pressure on LiDAR driver design. Hence, this work presents a gallium nitride (GaN)–Si hybrid integrated driver for a LiDAR system. In the circuit, the switching power device uses GaN instead of a Si-based device, because GaN enables much better performance for pulsed-laser operation due to its near-ideal switching performance. Furthermore, a GaN push–pull driver stage between the GaN power device and the Si-based driver integrated circuit (IC) was innovatively introduced, which is integrated in the same chip with the GaN power device, thereby effectively reducing the parasitic parameters of the signal chain and enhancing the system reliability. The design and implementation of the Si-based IC and GaN IC are based on 0.18 µm 80–120 V Bipolar-CMOS-DMOS (BCD) technology and 0.5 µm p-GaN technology, respectively. The experimental results suggest that the proposed driver circuit output pulse width is 12.6 ns, and it can normally operate at 10 MHz with turn-on/turn-off delay is 11.94 ns. In addition, the driver was capable of generating approximately 8.25 A current pulses through a low ohmic load with a pulse width of approximately 12.4 ns. This work plays a vital role in promoting the development of information equipment and aerospace equipment such as precise ranging, high-efficiency power supplies, and high-speed motors.